Peran Civil Society Dalam Pengelolaan Lingkungan Pesisir Kota Semarang: Studi Kasus Kelompok Prenjak dan Kelompok - anggun ari akbari; turtiantoro .; puji astuti (Journal of Politic and Government Studies, 2016)
Government of Semarang City is seeking adaptation to climate change in coastal areas such as rising sea levels each year that could threaten the existence of the land area and population. Adaptation measures are implemented to make coastal land-use planning with the aim of restoring its original shoreline affected by abrasion. One of the plans is the manufacture coastal embankment to be combined with the mangrove ecosystem that will establish the Green Belt. The Government will work with community groups concerned about the environment in the realization of these plans for coastal power of Semarang is based on the local community.This study will identify how the form of the power of the coastal city of Semarang is located on the local-based community. Shape in the form of the power of the role of civil society who formed a group concerned about the environment in realizing the management of coastal environments also able to empower communities, namely Prenjak Group in Tapak Tugurejo village and Camar Group in Tambakrejo Tanjung Mas village which is a case study of the research. Coastal environmental management program run by the main planting mangrove ecosystem that will become a tourist ecoedu concept is capable of being empowerment tool both for members and surrounding communities. In performing its role, both Prenjak Group and Camar Group will be influenced by several factors such as the capacity of individuals, capacity of community. assistance and training as well as support from various parties.These factors will form the potential, barriers and obstacles to the two groups that will affect the strength of the role itself. This type of research is descriptive qualitative analytical approach. Source of data derived from primary and secondary data.Determination of informants is through snowball sampling method to determine two types of informants. The first informant as key informants consisting of Prenjak Group and Camar Group. The second informant as informants triangulation consisting of DKP Kota Semarang and BAPPEDA Kota Semarang. In collecting the data,researchers used two methods: the method of interview and literature study.Key Words: Civil Society, Prenjak Group, Camar Group.